Pengaruh Kebiasaan Catcalling terhadap Kondisi Mental Santri Putri Usia Sekolah: Studi Kasus di Pondok Pesantren Darul Qura’an Wal Irsyad Wonosari - Lia Chikmatul Maula; Ollyvia Cahyaning Negari; Heni Tri Astuti (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2023)
This research aims to analyze the impact of catcalling habits on the mental condition of school-aged female students at Pondok Pesantren Darul Qur'an Wal Irsyad. The research methodology employed a combination of qualitative and quantitative approaches. Data were collected through surveys and interviews with female students of school age at the mentioned Islamic boarding school. The results of this study indicate that not all students feel comfortable when subjected to catcalling. The habit of catcalling can be considered demeaning to women, and it can harm their mental well-being. The quantitative findings reveal that a majority of the students feel disturbed by catcalling, while the qualitative data unveil various experiences and perceptions of the students regarding this phenomenon. This research provides a better understanding of the impact of catcalling habits on the mental condition of school-aged female students in Islamic boarding schools. The results can serve as a basis for the boarding school and the community to raise awareness about the importance of respecting women and avoiding behaviours that demean them. Furthermore, this research contributes to the literature on gender and mental well-being within the context of Islamic boarding schools in Indonesia.